A concise review on bioactive pentacyclic triterpenoids of Centella asiatica (Gotu Kola) - Kajim Ali; Sudhir Kumar; Mohammad Faheem Khan (Discover Chemistry)
Abstract Centella asiatica (L.) Urb. is a species of herbaceous plant native to the tropic and subtropical regions of Southeast Asia, China, and India. It is commonly referred to as "Gotu kola" in India. For hundreds of years, this well-known folk remedy has been used in Chinese and Indian traditional medicine to promote brain function, prevent cognitive impairments, and enhance memory. Major constituents with a range of pharmacological properties, such as antioxidant, anti-inflammatory, antibacterial, anticancer, hepatoprotective, immunomodulatory, neuroprotective, cardioprotective, and wound healing properties, have been identified as pentacyclic triterpenoids, including asiaticoside, madecassoside, asiatic acid, and madecassic acid. In the present work, we compiled the details from earlier literature containing research data regarding the isolation, purification, and pharmacological properties of 57 pentacyclic triterpenoids that were extracted from various parts of this plant using multiple chromatographic methods. The isolation yields, pharmacological properties, and structure–activity relationship (SAR) analysis are also addressed.